155 Impacts of post-weaning growth rate on reproductive development and maternal productivity of replacement beef heifers. (5th December 2019) - Schubach, Kelsey; Cooke, Reinaldo F; Brandão, Alice; Marques, Rodrigo; Bohnert, David
Abstract: The objective of this study was to compare growth, reproductive development, and productivity as primiparous in replacement beef heifers receiving diets to yield low (LGAIN), medium (MGAIN), and high (HGAIN) growth rates from weaning until their first breeding season. Seventy-two Angus × Hereford heifers weaned at 7 months of age were managed as a single group on pasture, and individually received supplements to achieve the desired average daily gain (ADG) until breeding (d 183). Accordingly, ADG was greater (P < 0.01) in HGAIN vs. MGAIN and LGAIN (0.85, 0.65, and 0.40 kg/d, respectively), and greater (P < 0.01) in MGAIN vs. LGAIN heifers. Puberty attainment until the breeding season was also greater in HGAIN vs. MGAIN and LGAIN (87, 65, and 56% pubertal heifers, respectively), but similar (P = 0.35) between MGAIN vs. LGAIN heifers. No differences were detected for pregnancy and final calving rate between treatments (P > 0.22), whereas HGAIN and MGAIN heifers were heavier (P = 0.05) at calving compared with LGAIN. Approximately 45 days after calving, milk production was estimated via weight-suckle-weight and milk samples collected from a subset of 10 heifers/treatment. Milk yield was less (P < 0.05) in LGAIN vs. MGAIN and HGAIN (5.0, 6.3, and 6.2 kg/d, respectively), and similar (P = 0.72) between MGAIN and HGAIN heifers. Expression of GLUT1 and GLUT9 in milk fat cells tended to be less (P < 0.09) in LGAIN vs. MGAIN and HGAIN, and similar (P = 0.33) between MGAIN and HGAIN heifers. At weaning, HGAIN and MGAIN heifers had heavier (P < 0.05) calves compared with LGAIN heifers (220, 214, and 206 kg, respectively), despite similar (P = 0.52) calf weaning age among treatments. Therefore, exposing replacement heifers to HGAIN hastened their reproductive development, without impairing milk productivity and calf weaning weight as primiparous cows.